Application of Metapopulation Theory to Northern Bobwhite Conservation - Joseph P. Sands; Stephen J. DeMaso; Leonard A. Brennan; Damon L. Williford; Randall W. DeYoung; Erin M. Wehland; Fidel Hernandez; Katherine S. Miller (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) populations have declined throughout the majority of the species’ range, and have experienced the largest declines in fragmented habitats, suggesting landscape scale processes may be responsible for this decline. We used the results from a stochastic population dynamics model of South Texas bobwhites as conceptual justification for use of metapopulation theory in bobwhite management. Annual quasi-extinction probabilities for isolated bobwhite populations were 0.003 (95% CI: 0.001 0.006), 0.105 (95% CI: 0.083 0.126), and 0.773 (95% CI: 0.750 0.796) for simulated populations harvested at 20, 30, and 40% annually. The probability of regional persistence at 30% harvest increased to ~ 100% in scenarios where we modeled 5 occupied hypothetical 800-ha habitat patches; however, at 40% harvest rates, probability of regional metapopulation persistence did not reach 95% until 12 habitat patches were occupied. This suggests bobwhites probably require somewhere from 800 to 9,600 ha of available habitat space to maintain 95% probability of regional metapopulation persistence as harvest varies from 0 to 40% annually. Our results have strong implications for bobwhite harvest management given the high probability of quasi-extinction of isolated populations at rates of harvest 25%. Multiple patches of habitat (where individual patch size is 800 ha) must be available to ensure bobwhite metapopulation persistence.
Keywords: Colinus virginianus; dispersal; metapopulation dynamics; northern bobwhite; simulation modeling